Kearifan Lokal tentang Mitigasi Bencana pada Masyarakat Baduy - Permana, Raden Cecep Eka; Nasution, Isman Pratama; Gunawijaya, Jajang (Makara Human Behavior Studies in Asia, 2011)
This study examines the indigenous Baduy society in preventing disaster. This study used a qualitative approach. Data collected by observation and depth interview methods, and analysis conducted by descriptive-analytical. This study aims to gain knowledge and traditional ways of Baduy society that has passed down from generation to generation. The results showed that (a) cut-and-burn systems in Baduy forests to open field for dry rice cultivation (huma) did not cause forest fires, (b) Baduy settlements adjacent to the river is not flooding, (c) houses and buildings made of materials combustible (wood, bamboo, thatch, and palm fiber) infrequent fires, and (d) Baduy territory included in the earthquake-prone areas of West Java, there is no damage to buildings due to the earthquake disaster. This is because the pikukuh (customary rules) that serve as guidelines and direction for Baduy think and act. Pikukuh are the basis of traditional knowledge that wise and prudent, so avoid the disaster.